Impact of ENSO events on meteorological drought in the Weihe River basin, China - Fan, Jingjing; Wei, Shibo; Liu, Dengfeng; Qin, Tianling; Xu, Fanfan; Wu, Chenyu; Liu, Guanpeng; Cheng, Yao (Frontiers in Earth Science, 2023)
El Niño-Southern Oscillation(ENSO) events influence elements of the terrestrial water cycle such as precipitation and temperature, which in turn have a significant impact on drought. This paper seeks to determine the impact of El Niño and La Niña on droughts from 1970 to 2020 in the Weihe River Basin (WRB) in China. This study uses a standardized precipitation index (SPI) to characterize meteorological drought. The regional drought response to extreme events in El Niño/La Niña is analysed using Principal Component Analysis (PCA), Wilcoxon Mann-Whitney test and other methods. The results show that, based on PCA, WRB is divided into two regions, with the northwest region (67%) accounting for more than the southeast region (33%).The drought mainly occurred in the El Niño year and the following year of La Niña. The number of drought years in El Niño was the highest (44%), followed by the next year of La Niña (43%), and the next year of El Niño (22%) was the least. On the time scales of 1,3 and 6 months, the significant drought mainly occurred from July to December in the El Niño year and the summer in the following year of La Niña. On a 12-month time scale, significant droughts mainly occurred from January to April in El Niño year, while no drought occurred in La Niña year. The longer the time scale of the SPI, the more months of significant drought occur in El Niño year, but the intensity of drought in the basin is reduced. In the following year of La Niña, summer drought intensifies on a 6-month timescale compared to a 3-month timescale. El Niño and La Niña have a greater impact on the drought index in the northwest of the WRB. In the northwest region, 60 % of the months have significant drought, while only 2 % of the months in the southeast region have significant drought, and the drought intensity in the northwest region is higher. This study can provide reference for drought management and early warning system in WRB, and support the solution of water shortage.